Evaluación de la producción de carne de ganado criollo patagónico - Nora Abbiati C; Eduardo Fernández T; José María Aulicino D; Rubén Martínez M; Diego Rodríguez C; Claudia Ferrari H (Revista MVZ Cordoba, 2012)
RESUMEN